Identification of a 3-Gene Prognostic Index for Papillary Thyroid Carcinoma - Zhong, Lin-Kun; Deng, Xing-Yan; Shen, Fei; Cai, Wen-Song; Feng, Jian-Hua; Gan, Xiao-Xiong; Jiang, Shan; Liu, Chi-Zhuai; Zhang, Ming-Guang; Deng, Jiang-Wei; Zheng, Bing-Xing; Xie, Xiao-Zhang; et al. (Frontiers in Molecular Biosciences, 2022)
The accurate determination of the risk of cancer recurrence is a critical unmet need in managing thyroid cancer. Although numerous studies have successfully demonstrated the use of high throughput molecular diagnostics in thyroid cancer prediction, it has not been successfully applied in routine clinical use, particularly in Chinese patients. In our study, we objective to screen for characteristic genes specific to PTC and establish an accurate model for diagnosis and prognostic evaluation of PTC. We screen the differentially expressed genes by Python 3.6 in The Cancer Genome Atlas (TCGA) database. We discovered a three-gene signature Gap junction protein beta 4 (GJB4), Ripply transcriptional repressor 3 (RIPPLY3), and Adrenoceptor alpha 1B (ADRA1B) that had a statistically significant difference. Then we used Gene Expression Omnibus (GEO) database to establish a diagnostic and prognostic model to verify the three-gene signature. For experimental validation, immunohistochemistry in tissue microarrays showed that proteins expressed by these three genes are differentially expressed in thyroid samples. Our protocol discovered a robust three-gene signature that can distinguish prognosis, which will have daily clinical application.